Turun linna - Jahnsson, Adolf Waldemar, 1841-1894 (Salt Lake City, UT : Project Gutenberg, 2016)
"Turun linna" by Adolf Waldemar Jahnsson is a historical account written during the mid-19th century. The book explores the history and significance of Turku Castle, tracing its origins and the various historical events that took place there, particularly during the medieval and early modern periods in Finland. It delves into the themes of power, conflict, and the transition of rule in the region, making it a comprehensive exploration of an important landmark in Finnish history. The narrative begins by recounting the construction of Turku Castle and the context of its establishment around the 12th century, during King Eerik's reign, emphasizing its role in the spread of Christianity in Finland. The book highlights the struggles for power between different factions, including the Swedes and Danes, and the internal conflicts that marked the region's history, such as the infamous Kalmar Union and subsequent rebellions. Through captivating anecdotes, Jahnsson depicts the lives of notable figures associated with the castle, including bishops and kings, ultimately painting a vivid picture of Turku Castle's importance as a symbol of authority and its transformation over the centuries. (This is an automatically generated summary.)
Release date is 2016-02-09
E-text prepared by Jari Koivisto
Keywords: Turun linna (Turku, Finland); Castles -- Finland -- Turku